An epidemiological trend in surgical management of pelvis and acetabulum fractures at Indira Gandhi Institute of Medical Sciences level-1 trauma centre in Patna: a retrospective study - Kumar, Rishabh; Kumar, Ashutosh; Shankar, Anand; Kumar, Rakesh (International Journal of Research in Medical Sciences, 2024)
Background: Pelvic and acetabular fractures, principally resulting from high-energy trauma like motor vehicle accidents, are challenging orthopedic injuries that can lead to significant morbidity and functional impairment. Understanding their epidemiology, treatment, and outcomes is crucial for improving patient care. Methods: This retrospective cohort study involving 34 patients who underwent surgery for pelvic and acetabular fractures from April 2021 to September 2023. Data on patient demographics, injury mechanisms, fracture types, surgical approaches, and post-operative outcomes were collected and analyzed. Results: The study group comprised predominantly males (67%) with mean age of 35 years. Road traffic accidents were the leading cause of injuries (95%). The most common fracture types were the posterior wall of the acetabulum (10%) and type II anteroposterior compression fractures (10%). Related injuries included long bone fractures (62.5%) and posterior hip dislocation (33.33%). Surgical treatment primarily involved open reduction and internal fixation with various approaches. Postoperative complications included sciatic nerve palsy (4.17%), venous thromboembolism (20.83%), and wound infections (12.5%), but both post-operative mortality and heterotopic ossification were absent. Conclusions: The study highlights the prevalence of pelvic and acetabular fractures due to road traffic accidents and the complexity of their surgical management. The associated injuries and postoperative complications underscore the need for specialized orthopedic care.